Atheism on Trial : a Lawyer Examines the Case for Unbelief. - Lanier, W. Mark (InterVarsity Press, 2022)
In the courtroom, lawyers establish certain facts to prove their cases. But can the legal mind discern the validity of one's belief or unbelief? With an even-handed approach, nationally recognized trial lawyer Mark Lanier explores whether atheistic frameworks give satisfactory answers for understanding human existence and considers the questions of agnostics as to whether God is knowable.